Medical ethics and professional training: building competencies for responsible healthcare practice - Celorio, Melany V.; Loor, Ivanna W.; Macías, Rosa M.; Molina, María N.; Moreira, Beatríz E.; Borroto, Eugenio R.; Herrera, María del R. (Revista Gregoriana de Ciencias de la Salud, 2025)
This essay aimed to analyze the importance of medical ethics in professional training for future physicians, emphasizing current challenges and proposing strategies to strengthen ethical competencies in clinical practice. Through a critical review of the literature and educational contexts in countries such as Ecuador, the paper identifies weaknesses in bioethics programs and calls for a comprehensive approach that incorporates both technological advancements and humanistic values. It recommends reinforcing curricula with practical modules, fostering medical professionalism, and establishing ethics committees within academic institutions to promote a more just, empathetic, and responsible healthcare practice.